Czerwony Atlantyk? - Waldemar Kuligowski (Journal of Folklore and Popular Culture)
Recenzja: Caroline Dodds Pennock, On Savage Shores. How Indigenous Americans Discovered Europe, Wedenfeld-Nicolson, London 2023.